Knowledge of Saudi Patients with Autoimmune Diseases about Hydroxychloroquine Toxicity: The Role of Physician-Patient Communication - Amal Aldarwesh; Ali Almustanyir; Mazoon Alharthi; Duja Alhayan (MDPI AG, 2022)
This cross-sectional internet-based questionnaire aimed to assess the knowledge and experience of autoimmune disease patients in Saudi Arabia of the ocular effects of hydroxychloroquine (HCQ). Among the 245 respondents, discontinuation of the drug was linked to its ocular toxicity in approximately 7.3%. Most patients had taken HCQ for a period longer than five years, exceeding a dose of 5 mg/Kg. A lack of education and physician communication about medication toxicity was reported by approximately 40.8% of the participants. Despite the knowledge about HCQ retinopathy, the drug is prescribed to autoimmune disease patients at an inappropriate dosage. Knowledge obtained from physicians' communication may improve the health outcomes of chronically ill patients. Rheumatologists and ophthalmologists should work together to recognize patients at risk of hydroxychloroquine toxicity and ensure they receive proper education and adhere to periodic follow-up.